The Language of Engagement: Speech Functions and Mood in the Berkeley Exec Ed Podcast - Silaban, Jelly Prima Krisnawati; Azzahra, Sekar; Nurlela (Universitas Pamulang, 2025)
This paper investigates the interpersonal functions in the discourse of the Berkeley Exec Ed podcast, specifically the episode